Nursing care for parents who have experienced fetal demise: integrative review - Nycarla de Araújo Bezerra; Cibelle Nayara Sena dos Santos; Adrian Thaís Cardoso Santos Gomes da Silva; Francisca Márcia Pereira Linhares; Sheila Coelho Ramalho Vasconcelos Morais (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to identify scientific evidence regarding nursing care for parents who have experienced grief following fetal demise. Methods: an integrative review of original studies was conducted across six databases. The studies were classified according to the level of evidence. Results: the qualitative analysis of the nine studies comprising the sample involved thematic categories, exploring the impact of perinatal loss on families, inadequate communication by healthcare professionals, and the importance of a holistic approach in care. The role of the nurse is highlighted in making a positive contribution to the team, emphasizing participation in training and the provision of essential information. Final Considerations: grieving affects not only family dynamics but also the social environment, emphasizing the urgency of a more empathetic and comprehensive approach. Care should be holistic, going beyond technical nursing assistance, and addressing the biopsychosocial context of the parents.